1975
DOI: 10.1104/pp.55.2.178
|View full text |Cite
|
Sign up to set email alerts
|

Differential Regulation of Nitrate Reductase Induction in Roots and Shoots of Cotton Plants

Abstract: The induction of nitrate reductase activity in root tips of cotton (Gossypium hirsutum L.) was regulated by several amino acids and by ammonium. Glycine, glutamine, and asparagine strongly inhibited induction of activity by nitrate and also decreased growth of sterile-cultured roots on a nitrate medium. Methionine, serine, and alanine weakly inhibited induction, and 11 other amino acids had little or no effect. Ammoniuni also decreased induction in root tips, but was most effective only at pH 7 or higher. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

1976
1976
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(16 citation statements)
references
References 25 publications
2
14
0
Order By: Relevance
“…Regardless, aspartic and glutamic acids apparently behaved differently from other amino acids. This conclusion is consistent with earlier studies (15).…”
Section: Methodssupporting
confidence: 94%
See 1 more Smart Citation
“…Regardless, aspartic and glutamic acids apparently behaved differently from other amino acids. This conclusion is consistent with earlier studies (15).…”
Section: Methodssupporting
confidence: 94%
“…Procedures were similar to those described earlier (15). Seeds of cotton (Gossypium hirsutum L. Table I presents a summation of many experiments in which amino acids were applied singly or in pairs to root tips during induction of NR activity.…”
Section: Methodsmentioning
confidence: 99%
“…The situation is less clear in higher plants. Ammonium has heen reported to inhibit the induction of nitrate reductase in barley roots (Smith and Thom^pson, 1971a) and in roots, but not shoots of cotton plants (Radin, 1975). Ammonium inhihition of the formation of nitrate reductase activity has been well estahlished for Lemna minor L. (Joy, 1969;Orehamjo andStewart, 1974, 1975).…”
Section: Discussionmentioning
confidence: 99%
“…The results for the possible regulation of NR activity by amino acids for higher plants are contradictory. Many authors agree with that amino acids can inhibit the activity of NR in higher plants (Radin, 1975(Radin, , 1977Oaks et al, 1979;Ivashikian and Sokolov, 1997;Sivasankar et al, 1997;Aslam et al, 2001). But Aslam et al (2001) reported that inhibition did not occur when the concentration of NO 3 -in the external solutions had been increased to 10 mM.…”
Section: Effect Of Aaf On Enzyme Activitiesmentioning
confidence: 99%
“…In studies of the possible regulation of NR activity by amino acids in higher plants, the results have often been conflicting. For example, Radin (1975Radin ( , 1977 had shown that the reduction of nitrate to nitrite in cotton roots is inhibited by specific amino acids. On the other hand, Oaks (1977) had found using an in vitro assay those amino acids results in enhanced levels of NR and also cause only minor inhibitions in both intact and excised corn roots.…”
Section: Amino Acids and Enzyme Regulationmentioning
confidence: 99%